2015
DOI: 10.1021/ed500726y
|View full text |Cite
|
Sign up to set email alerts
|

An Easy-To-Assemble Three-Part Galvanic Cell

Abstract: The galvanic cell presented in this article is made of only three parts, is easy to assemble, and can light a red light emitting diode (LED). The three cell components consist of a piece of paper with copper sulfate, a piece of paper with sodium sulfate, and a piece of magnesium ribbon. Within less than 1 h, students have time to discuss the function of the main battery parts, construct the cell, and test it with a LED. This low cost laboratory activity is suited to most general chemistry curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…This includes examining difficulties students have learning the science content, their affective views regarding the content, and instructors’ perspectives on how to evaluate students’ learning of the science content. In this component, we reviewed research on misconceptions, alternative views, and sources of these that students have about electrochemistry and batteries. To better understand instructors’ perspectives on assessing student understanding of electrochemistry and battery concepts, we reviewed studies of instructors’ topic-specific knowledge of electrochemistry, , and approaches that have been taken by others to address electrochemistry learning. We also examined studies that specifically addressed electrochemistry and batteries in terms of students’ attitudes and views. …”
Section: Introductionmentioning
confidence: 99%
“…This includes examining difficulties students have learning the science content, their affective views regarding the content, and instructors’ perspectives on how to evaluate students’ learning of the science content. In this component, we reviewed research on misconceptions, alternative views, and sources of these that students have about electrochemistry and batteries. To better understand instructors’ perspectives on assessing student understanding of electrochemistry and battery concepts, we reviewed studies of instructors’ topic-specific knowledge of electrochemistry, , and approaches that have been taken by others to address electrochemistry learning. We also examined studies that specifically addressed electrochemistry and batteries in terms of students’ attitudes and views. …”
Section: Introductionmentioning
confidence: 99%
“…It only shows up with a simple introduction where students can hardly imagine the movement process of the particulates in the electrodes and solution to understand the reaction principle . Many works published in this Journal are normally focused on teaching experiments of electrochemistry, including some novel experiments about the primary cell. However, there are few works focusing on concentration cell experiments. Here we choose concentration cells as the topic in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its usefulness, a series of classroom activities, demonstrations and laboratories have been previously introduced for the purpose of demonstrating electrochemical applications in real life situations using easily accessible materials. [1][2][3][4][5][6][7][8][9][10][11] Although pivotal, grasping electrochemical concepts correctly has been traditionally difficult for students in high school and introductory courses at the university level. Several reports have demonstrated that there are well-established electrochemical misconceptions among students.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical concepts are of importance to all students majoring in science and engineering fields, as electrochemistry is a gateway to the understanding of energy storage (batteries), energy production (fuel cells), and materials selection (corrosion). Due to its usefulness, a series of classroom activities, demonstrations, and laboratories have been previously introduced for the purpose of demonstrating electrochemical applications in real life situations using easily accessible materials. …”
Section: Introductionmentioning
confidence: 99%